THE FUTURE OF DIGITAL BRANDING THROUGH GENERATIVE MEDIA - S. Balaji; Bhargav, Shilpa; Tewatia, Nidhi; Dash, Banashree; Meena, Smita; Sriram, Siddharth; Bhapkar, Archana Haribhau (ShodhKosh: Journal of Visual and Performing Arts, 2025)
A major change in digital branding in the future is the accelerated generation of generative media which includes image creation and video making, and audio creation and narrative systems founded on text. As expanding brands operate within algorithmic, hyper-personal and interacting space, generative technologies present unmatched potential in the creation of dynamic, responsive and emotionally charged brand experiences. In this paper, the concept of generative media as the means of altering the brand identity formation, consumer perception, and storytelling is discussed in terms of its ability to enable scalable creativity, allow content to be varied in real-time and enable brand to be transformed over time. The changes in the field of emotional branding, the participatory culture in the digital world, and psychology of personalized experiences with the media are reflected in the theoretical bases. We also talk about the technological background of the work GANs, diffusion models, and transformer-based architectures which can be applied to provide adaptive pipelines to create context-sensitive brand assets. More and more, with the developing case studies, we evaluate the contribution of generative systems towards offering greater engagement, flexibility of the narrative, and the assistance of constructing virtual influencers and responsive brand avatars. The analysis of the quantitative and qualitative impact may indicate a balance shift between brand consistency and creative variability on what AI-generated content may be able to reinforce the trust, increase consumer immersion, and accelerate the designing processes when addressed accordingly.